First report of the scavenging isopod Natatolana neglecta (Crustacea: Isopoda: Cirolanidae) feeding on a sea turtle - REVUELTA, OHIANA; DOMÈNECH, FRANCESC; KEABLE, STEPHEN; MÍGUEZ-LOZANO, RAÚL (Mediterranean Marine Science, 2019)
A juvenile male loggerhead sea turtle (Caretta caretta) was found dead in April 2015, entangled in a trammel net on the Mediterranean coast of Spain. Post-mortem examination revealed the presence of ninety-five isopods dispersed in the coelomic cavity, and inside the oesophagus and skull. All individuals found scavenging on the sea turtle were identified as Natatolana neglecta (Hansen, 1890) (Isopoda: Cirolanidae). Genetic analysis of the isopod gut contents showed that they were feeding on turtle tissue, confirming that N. neglecta can also attack dead sea turtles. This study shows the value of cirolanids as potential indicators of the cause of death in stranded sea turtles.